2013
DOI: 10.1149/ma2013-02/28/2046
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Lead Sulfide Thin Film and Application As Counter Electrode for Quantum Dot Solar Cells

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, potential interest rapidly increased for the preparation of PbS thin films by different techniques. Authors have reported different results based on the implementation techniques by using atomic layer deposition (ALD) [ 9 ], solid vapor deposition [ 10 ], thermal evaporation method [ 11 ], RF sputtering [ 12 ], spray pyrolysis [ 13 ], and electro-deposition [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, potential interest rapidly increased for the preparation of PbS thin films by different techniques. Authors have reported different results based on the implementation techniques by using atomic layer deposition (ALD) [ 9 ], solid vapor deposition [ 10 ], thermal evaporation method [ 11 ], RF sputtering [ 12 ], spray pyrolysis [ 13 ], and electro-deposition [ 14 ].…”
Section: Introductionmentioning
confidence: 99%